Revitalisasi Tradisi Lokal sebagai Sumber Belajar IPAS di Sekolah Dasar SDN 4 Sila - Yamin, Muhammad (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to analyze the revitalization of local traditions as learning resources in Social and Natural Sciences (IPAS) instruction at SDN 4 Sila. The research stems from the low utilization of local traditions in IPAS learning, despite the high educational potential of local culture in developing students’ knowledge, attitudes, and social skills. Local traditions rich in wisdom, social norms, and cultural practices are considered capable of connecting learning to students’ real-life contexts, thereby enhancing its relevance and quality. Using a qualitative approach with a descriptive method, the study involved IPAS teachers, community leaders, and students, with data collected through observations, interviews, and documentation. The findings indicate that local traditions hold great potential as IPAS learning resources, especially in fostering social competence, cultural values, and understanding of space and time, although teachers have not maximized their use due to limited pedagogical knowledge and a lack of culturally integrated teaching materials. Revitalizing local traditions through integration into learning modules, culture-based media, and collaboration with community leaders has proven to increase student engagement, understanding of IPAS concepts, and appreciation for local culture. The study concludes that utilizing local traditions as learning resources is an effective strategy for improving IPAS learning quality in elementary schools and emphasizes the need for systematic revitalization through the development of teaching materials, teacher training, and school–community partnerships.